2014
DOI: 10.1016/j.neuroimage.2014.06.061
|View full text |Cite
|
Sign up to set email alerts
|

Why we interact: On the functional role of the striatum in the subjective experience of social interaction

Abstract: There is ample evidence that human primates strive for social contact and experience interactions with conspecifics as intrinsically rewarding. Focusing on gaze behavior as a crucial means of human interaction, this study employed a unique combination of neuroimaging, eye-tracking, and computer-animated virtual agents to assess the neural mechanisms underlying this component of behavior. In the interaction task, participants believed that during each interaction the agent's gaze behavior could either be contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
121
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(140 citation statements)
references
References 85 publications
16
121
1
2
Order By: Relevance
“…Even unaddressed participants, who do not take a turn in the question-response sequences in our data, show evidence in their gaze behavior of a fine attunement to this feature of the turn-taking system 4 . Our findings that unaddressed participants' gaze behavior during question-response sequences appears to be organized according to a principle that optimizes recipiency also fits well with the notion of an 'intrinsic motivation for participation,' as it were Pfeiffer et al, 2014). Both Schilbach et al (2010) and Pfeiffer et al (2014) demonstrate that, in the context of gaze-based interactions, humans experience social-interactional engagement as rewarding, as evidenced by cerebral activity patterns in reward-related neurocircuitry.…”
Section: Optimizing Recipiencysupporting
confidence: 74%
“…Even unaddressed participants, who do not take a turn in the question-response sequences in our data, show evidence in their gaze behavior of a fine attunement to this feature of the turn-taking system 4 . Our findings that unaddressed participants' gaze behavior during question-response sequences appears to be organized according to a principle that optimizes recipiency also fits well with the notion of an 'intrinsic motivation for participation,' as it were Pfeiffer et al, 2014). Both Schilbach et al (2010) and Pfeiffer et al (2014) demonstrate that, in the context of gaze-based interactions, humans experience social-interactional engagement as rewarding, as evidenced by cerebral activity patterns in reward-related neurocircuitry.…”
Section: Optimizing Recipiencysupporting
confidence: 74%
“…In addition, different lines of research implicate dysfunction of striatal neurocircuitry in schizophrenia, which has been associated with impairments of wanting, liking and learning and could be particularly relevant for social interaction, as it has been shown that successful and enjoyable participation in social interaction significantly draws upon these neurocircuits [22,49]. Mesolimbic dopamine circuitry has been shown to play a role in so-called 'wanting' responses in animals and humans, i.e.…”
Section: (D) the Case Of Schizophreniamentioning
confidence: 99%
“…interaction may be intrinsically rewarding; Mundy and Neal, 2000;Schilbach et al, 2010;Pfeiffer et al, 2014), one component of successful social interaction is the creation of a shared psychological state between partners (Clark, 1996;Sperber and Wilson, 1996;Tomasello et al, 2005). Consistent with this perspective, recent behavioral (e.g.…”
Section: Introductionmentioning
confidence: 98%
“…Adult neuroimaging research has begun to identify the neural bases of social interaction (e.g. Redcay et al, 2010;Schilbach et al, 2010;Pö nk€ anen et al, 2011;Pfeiffer et al, 2014;Rice and Redcay, 2016), but few studies have investigated how the developing brain supports social interaction. Understanding the developmental bases of realworld social behaviors will provide insight into both typical and atypical social development, where disorders such as autism and social anxiety are characterized by interpersonal difficulties (e.g.…”
Section: Introductionmentioning
confidence: 99%